Unique Neural Circuitry for Neonatal Olfactory Learning - Moriceau, Stephanie (Society for Neuroscience, 2004)
Imprinting ensures that the infant forms the caregiver attachment necessary for altricial species survival. In our mammalian model of imprinting, neonatal rats rapidly learn the odor-based maternal attachment. This rapid learning requires reward-evoked locus ceruleus (LC) release of copious amounts of norepinephrine (NE) into the olfactory bulb. This imprinting ends at postnatal day 10 (P10) and is associated with a dramatic reduction in reward-evoked LC NE release. Here we assess whether the functional emergence of LC α2 inhibitory autoreceptors and the downregulation of LC α1 excitatory autoreceptors underlie the dramatic reduction in NE release associated with termination of the sensitive period. Postsensitive period pups (P12) were implanted with either LC or olfactory bulb cannulas, classically conditioned with intracranial drug infusions (P14), and tested for an odor preference (P15). During conditioning, a novel odor was paired with either olfactory bulb infusion of aβ-receptor agonist (isoproterenol) to assess the target effects of NE or direct LC cholinergic stimulation combined with α2 antagonists and α1 agonists in a mixture to reinstate neonatal levels of LC autoreceptor activity to assess the source of NE. Pups learned an odor preference when the odor was paired with either olfactory bulb isoproterenol infusion or reinstatement of neonatal LC receptor activity. These results suggest that LC autoreceptor functional changes rather than olfactory bulb changes underlie sensitive period termination.